2019
DOI: 10.1002/fsn3.903
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bergamot: From anti‐inflammatory and anti‐oxidative mechanisms to clinical applications as preventive agent for cardiovascular morbidity, skin diseases, and mood alterations

Abstract: We summarize the effects of bergamot (extract, juice, essential oil, and polyphenolic fraction) on cardiovascular, bone, inflammatory, skin diseases, mood alteration, anxiety, pain, and stress. This review included a total of 31 studies (20 studies on humans with 1709 subjects and 11 in animals (rats and mice)). In humans, bergamot‐derived extract (BE) exerts positive effects on hyperlipidemia with an oral dose from 150 mg to 1000 mg/day of flavonoids administered from 30 to 180 days, demonstrating an effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
1
33
0
1
Order By: Relevance
“…In addition, the high-fat diet leads also to a hepatic steatosis condi-tion, which can evolve into fibrosis and hepatic cirrhosis, and to a low-grade, systemic and chronic inflammatory state [29][30][31]. Several pre-clinical studies showed that C. bergamia promotes significant anti-inflammatory effects both at a systemic and tissue level [18,32]. Interestingly, Parafati et al reported in rats treated with a cafeteria diet, anti-inflammatory effects of a bergamot polyphenol fraction, recovering from NASH [18].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high-fat diet leads also to a hepatic steatosis condi-tion, which can evolve into fibrosis and hepatic cirrhosis, and to a low-grade, systemic and chronic inflammatory state [29][30][31]. Several pre-clinical studies showed that C. bergamia promotes significant anti-inflammatory effects both at a systemic and tissue level [18,32]. Interestingly, Parafati et al reported in rats treated with a cafeteria diet, anti-inflammatory effects of a bergamot polyphenol fraction, recovering from NASH [18].…”
Section: Resultsmentioning
confidence: 99%
“…In a clinical trial involving hypercholesterolemic patients, administration of naringin (400 mg/day, for 8 weeks) reduced plasma LDL-C and serum apoB by more than 14%, without altering plasma TG or HDL-C levels [218]. Naringenin found in bergamot inhibits LDL oxidation, initiates AMPK, modulates the activation of redox-sensitive transcription factors NF-κB induced by TNF-α and acts as ROS scavenger [219]. There are reports showing that hesperetin-induced eNOS expression increased NO production via phosphorylation of Src, Akt and AMPK in cultured EC, and consequently prevented hypertension by improving endothelial dysfunction in the hypertensive rat [220,221].…”
Section: Flavanonesmentioning
confidence: 99%
“…Over the last decades, new hypothesis emerged on the possible favorable anti‐inflammatory and hypolipidemic properties of bergamot derivatives (Spigoni et al, ). However, there is a lack of information on the specific phenolic metabolite that might be responsible of the biological activity of bergamot (Perna et al, ). To address this issue, we conducted a randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐escalation, clinical trial on a large sample of overweight subjects with mildly hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%